2006
DOI: 10.1007/s12015-006-0009-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of stem cells in physiology, pathophysiology, and therapy of the liver

Abstract: The objectives of the present review is to update readers with the rapidly changing concepts in liver stem cell biology and related clinical applications. The liver has adapted to the inflow of ingested toxins by the evolutionary development of unique regenerative properties and responds to injury or tissue loss by rapid division of the mature cells, hepatocytes, and bile duct epithelial cells. Proliferation of the parenchymal cells is regulated by numerous cytokine/growth factor-mediated pathways and is timel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 87 publications
0
23
0
Order By: Relevance
“…Hamazaki and coworkers were among the first to generate a high percentage of hepato-hepatic phenotype in the last years (1,8,22,25,29,31,33,34,37). However, most of the currently available data cyte precursors from murine ES cell cultures in the presence of growth factors (10).…”
Section: Introductionmentioning
confidence: 99%
“…Hamazaki and coworkers were among the first to generate a high percentage of hepato-hepatic phenotype in the last years (1,8,22,25,29,31,33,34,37). However, most of the currently available data cyte precursors from murine ES cell cultures in the presence of growth factors (10).…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Consequently, despite their quiescent state, hepatocytes may be considered functional liver stem cells, with very high clonogenic potential, as demonstrated by serial transplantation experiments. 17 In parallel to what we know from these rodent models, inhibition of replication of mature hepatocytes also exist in human liver diseases. Recently, it has been shown that hepatocytes are senescent owing to telomere shortening, in the cirrhotic stage of a wide variety of chronic human liver diseases.…”
Section: The Role Of Liver Stem/progenitor Cells In Chronic Liver Dismentioning
confidence: 94%
“…In addition to stem cell mobilizing strategies [56] and bioartificial liver devices (BAL) [78], several alternative cell-based therapies have been investigated to recover unstable conditions in chronic liver disorders as well as during metabolic or acute liver failure. In general the disorders are treated by transplantation of bone marrow hematopoietic, mesenchymal, and mononuclear cell populations (for review see [93] and [74]). The first evidence indicating MSC infusion in mice models could recover liver failure was suggested by Petersen et al showing the presence of bone marrow-derived hepatic cells from sex-mismatched donors in the recipient mice livers [65].…”
Section: Mscs In Liver Regenerationmentioning
confidence: 99%